Louie Louie : The History and Mythology of the World's Most Famous Rock 'n Roll Song; Including the Full Details of Its Torture and Persecution at the Hands of the Kingsmen, J. Edgar Hoover's FBI, and a Cast of Millions; and Introducing for the First Time Anywhere. - Marsh, Dave (University of Michigan Press Ebsco Publishing [distributor], 2010)
Since his days as the original editor ofCreem,Dave Marsh has been revered as one of rock's greatest critics. During the 70s he was record editor atRolling Stone,and in 1983 he foundedRock & Roll Confidential.His other books includeGlory Days: Bruce Springsteen in the 1980s(1987), andBefore I Get Old: The Story of the Who(1983).